2022
DOI: 10.3390/molecules27093009
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside: A Review of Its Structure, Synthesis, Pharmacology, Pharmacokinetics and Toxicity

Abstract: Hyperoside is an active ingredient in plants, such as Hypericum monogynum in Hypericaceae, Crataegus pinnatifida in Rosaceae and Polygonum aviculare in Polygonaceae. Its pharmacologic effects include preventing cancer and protecting the brain, neurons, heart, kidneys, lung, blood vessels, bones, joints and liver, among others. Pharmacokinetic analysis of hyperoside has revealed that it mainly accumulates in the kidney. However, long-term application of high-dose hyperoside should be avoided in clinical practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 80 publications
0
35
0
Order By: Relevance
“…Rutin’s pharmaceutical characteristics are studied best among all quercetin glycosides: this compound promotes mammalian smooth muscle relaxation [ 40 ], and rutin’s antioxidant effect protects hepatic cells [ 41 ], inhibits hemoglobin oxidation [ 42 ], and exerts an anti-inflammatory action [ 43 , 44 ]. Large reviews regularly mention the biological activity and therapeutic features of such quercetin glycosides as quercitrin [ 45 ], isoquercitrin [ 46 ], hyperoside [ 47 ], and reynoutrin [ 48 ]; some authors focus on the pharmacological activity of its methyl-containing derivative, isorhamnetin [ 49 ]. Nonetheless, quercetin derivatives that are less common in plants have attracted much attention.…”
Section: Resultsmentioning
confidence: 99%
“…Rutin’s pharmaceutical characteristics are studied best among all quercetin glycosides: this compound promotes mammalian smooth muscle relaxation [ 40 ], and rutin’s antioxidant effect protects hepatic cells [ 41 ], inhibits hemoglobin oxidation [ 42 ], and exerts an anti-inflammatory action [ 43 , 44 ]. Large reviews regularly mention the biological activity and therapeutic features of such quercetin glycosides as quercitrin [ 45 ], isoquercitrin [ 46 ], hyperoside [ 47 ], and reynoutrin [ 48 ]; some authors focus on the pharmacological activity of its methyl-containing derivative, isorhamnetin [ 49 ]. Nonetheless, quercetin derivatives that are less common in plants have attracted much attention.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, further investigation is required to evaluate the role of Hyp as an active constituents of Artemisia capillaris —a well-known herbal plant frequently used for treating liver disease [ 104 ]. In addition, based on above medicinal plants containing Hyp, further studies on efficient and economic extraction methods maximizing the purity and yield are needed [ 14 , 95 ]. Hence, Hyp may be an active compound present in various herbal plants that can be widely applied in clinical settings owing to its hepatoprotective, antiviral, antisteatotic, anti-inflammatory, antifibrotic, and anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, a few studies have investigated the safety of Hyp [ 14 , 95 ]. In 40 healthy BALB/c mice, Hyp treatment (5,000 mg/kg, intragastrical route once) did not result in mouse poisoning, death, acute toxicity, or genotoxicity [ 96 ].…”
Section: Safety Of Hyperosidementioning
confidence: 99%
“…Hyperoside (Hyp) is a kind of flavonoid compound extracted from many plants, such as Hypericum perforatum L. Flavonoid compounds have been proven to contribute to the treatment of CVD ( Russo et al, 2019 ; Parmenter et al, 2020 ; Gao et al, 2021 ). Some researchers found that Hyp preconditioning reduced the myocardial infraction area and the apoptotic rate in rats, the mechanism of which was likely to be anti-lipid peroxidation, anti-free radical synthesis, and anti-apoptosis ( Xu et al, 2022 ). Recently, a study revealed the effect of Hyp on H/R-induced cell injury by suppressing Bcl-2-interacting protein 3 (Bnip3) expression ( Xiao et al, 2017 ).…”
Section: Herb Medicines and Their Active Chemical Ingredients In Tcm ...mentioning
confidence: 99%